2015
DOI: 10.2527/jas.2014-8328
|View full text |Cite
|
Sign up to set email alerts
|

Growth promoting hormonal implant pellets coated with a polymeric, porous film promote weight gain by grazing beef heifers and steers for up to 200 days

Abstract: Two studies evaluated growth promoting effects of implant pellets (IP), each containing 3.5 mg estradiol benzoate (EB) and 25 mg trenbolone acetate (TBA), to which a polymeric, porous coating was applied. Trial 1 evaluated performance of heifers (n = 70/treatment, initial BW = 188 ± 2.2 kg) and steers (n = 70/treatment, initial BW = 194 ± 2.2 kg) implanted subcutaneously in the ear with 0 (SC), 2 (2IP), 4 (4IP), or 6 (6IP) pellets that delivered EB/TBA (mg/mg) doses of 0/0, 7/50, 14/100, and 21/150, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Cleale et al (2012) showed that addition of the polymer coating to 8-pellet implants containing 28 mg of estradiol benzoate and 200 mg of trenbolone acetate effectively modified payout of estradiol benzoate and trenbolone acetate from approximately 120 d for traditional uncoated implants (Synovex Plus; Zoetis) to up to 200 d with coated implants containing the same doses of active ingredients (Synovex One Feedlot; Zoetis). Later, Cleale et al (2015) showed in pastured steers implanted with SOG that ADG increased over 200-d grazing periods by 20.5% compared with sham-implanted controls in one study and 16.7% in a second study, results that are similar to the present study. Data pooled from 4 studies conducted to evaluate product efficacy showed that over 107-to 116-d grazing periods, ADG by steers treated with REVG (0.94 kg/d) was 14.6% more than ADG by negative controls (0.82 kg/d; FDA, 1996), a result similar to the effect of REVG in the present study.…”
Section: Bw Weight Gain and Adgsupporting
confidence: 88%
See 4 more Smart Citations
“…Cleale et al (2012) showed that addition of the polymer coating to 8-pellet implants containing 28 mg of estradiol benzoate and 200 mg of trenbolone acetate effectively modified payout of estradiol benzoate and trenbolone acetate from approximately 120 d for traditional uncoated implants (Synovex Plus; Zoetis) to up to 200 d with coated implants containing the same doses of active ingredients (Synovex One Feedlot; Zoetis). Later, Cleale et al (2015) showed in pastured steers implanted with SOG that ADG increased over 200-d grazing periods by 20.5% compared with sham-implanted controls in one study and 16.7% in a second study, results that are similar to the present study. Data pooled from 4 studies conducted to evaluate product efficacy showed that over 107-to 116-d grazing periods, ADG by steers treated with REVG (0.94 kg/d) was 14.6% more than ADG by negative controls (0.82 kg/d; FDA, 1996), a result similar to the effect of REVG in the present study.…”
Section: Bw Weight Gain and Adgsupporting
confidence: 88%
“…Finally, of 320 ENC steers observed on d 70, implants were located in 281, yielding a retention rate of 87.8%. The number of cattle with retained implants on d 70 was different across treat- Cleale et al (2015), where SOG implant retention rates in cattle treated by the same procedures as those used herein were 100 and 97.6%, respectively. Previous studies evaluating implant retention in cattle treated with estradiol-containing silicone implants have reported similar results to those reported here (Mathison and Stobbs, 1983).…”
Section: D-70 Implant Observationsmentioning
confidence: 81%
See 3 more Smart Citations